Analysis of Stem Anatomical Structure in Tomato (Solanum lycopersicum) - Sanjayanti, Arum; Ahmad, Deni Nasir; Adawiyah, Khumairoh; Putri, Nurul Lia; Putri, Bella Vista Rammanda (Journal of Biological Science and Education, 2024)
The tomato plant (Solanum lycopersicum) is native to the Americas, from the area around Mexico to Peru. Tomato stems, although not as hard as perennial plants, are quite strong. The color of the stem is green and is rectangular to round. The research method as well as analyzing the structure of tomato stems using descriptive methods. The research is descriptive analysis. Sampling was carried out at 16.00 WIB and only used one sample of tomato plant species and then made observations using a microscope with the help of section preparations. The data analysis technique used is a qualitative descriptive analysis model, where the model is included in the type of qualitative research described descriptively. The results showed that young tomato (Solanum lycopersicum) stems observed through a microscope with a magnification of 10x can be seen that only the epidermis, the cortex area (without being able to distinguish the tissue contained in the area), the transport tissue (without being able to know the location of xylem, phloem and other tissues) and the pith area where in this area the perenkim tissue is clearly visible.  Keywords:  Stem Anatomy, Solanum lycopersicum, Plant Tissue